THE RELATIONSHIP BETWEEN SELF-EFFICACY AND SELF-REGULATED LEARNING AND ACADEMIC PROCRASTINATION IN FINAL-YEAR STUDENTS AT SEMARANG STATE UNIVERSITY - Pramodha Wardhani; Sigit Hariyadi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Academic procrastination is a common problem experienced by students, especially during the final assignment or thesis completion stage. This behavior can be influenced by various psychological factors, including self-efficacy and self-regulated learning. This study aims to analyze the relationship between self-efficacy and self-regulated learning with academic procrastination in final-year students at UNNES. This study used a quantitative approach with a correlational design. The research sample consisted of 293 final-year students selected using a purposive sampling technique. Data were collected using a self-efficacy scale, a self-regulated learning scale, and an academic procrastination scale. Data analysis was performed using multiple linear regression. The results of the analysis showed that self-efficacy had a beta coefficient of -0.172 with a significance value of 0.000 (p <0.05). This indicates that self-efficacy has a negative and significant effect on academic procrastination. The self-regulated learning variable has a beta coefficient value of -0.675 with a significance value of 0.000 (p <0.05). This indicates that self-regulated learning has a negative and significant effect on academic procrastination and is the most dominant variable in predicting students' academic procrastination. The novelty of this research lies in the empirical finding that, in the context of final-year students completing their theses, self-regulated learning has a more dominant influence than self-efficacy in predicting academic procrastination. The results of this study are expected to serve as a basis for the development of guidance and counseling services in higher education institutions to help students manage their learning process more effectively.